Optimization of Irrigation for Potato with Microsprinkler Irrigation System - Kumar, Satyendra; Singh, Rajbir; Nangare, D D; Gupta, R K (Journal of Agricultural Engineering, 2008)
Water application for agriculture in semi-arid areas should be limited because of scare resources. An effort was made at Central Institute of Post Harvest Engineering and Technology, Abohar to determine the optimal water allocation to potato crop with micro sprinkler irrigation system. In this study, crop production and cost functions for potato were derived from field data and analyzed for determination of amount of water required to attain the maximum yield potential and profit. Results of the study indicated higher yield at I4 (1.2 Ep) irrigation level, whereas water use efficiency was found to be maximum at I3 (1.0 Ep). Derived relationship revealed that 280 mm ofwater (average value of two years) is required to get maximum potato yield with microsprinkler irrigation system under semi arid environment. Further, present study clearly indicated that reduction in water application from 280 mm (water level for maximum yield) to 247 mm (water level for maximum profit) increased net profit by 7%. When land is not a constraint, the saved water could be used to bring 12% more area under irrigation with micro sprinkler irrigation system to enhance the farmer’s income.